Determination of the baseline tritium concentrations (HTO, TFWT and OBT) in soil and plants in Ontario, Canada. (March 2022) - Kim, S.B.; Bredlaw, M.; Rousselle, H.; Bond, M.; Stuart, M.
Abstract: Tritiated water (HTO), tissue free water tritium (TFWT) and organically bound tritium (OBT) activity concentrations in soil and plant leaves, collected at background areas in Ontario, were measured to quantify the current tritium baseline. Five representative background sites, based on their geological characteristics and residential populations, have been selected for this study. Undisturbed soils, plant leaves and surface water samples were collected at 5 sites (London, Kapuskasing, Thunder Bay, Elliot Lake and Cornwall areas) in 2015. Water sample HTO activity concentrations were measured using Liquid Scintillation Counting (LSC, ALOKA), and HTO activity concentrations for soil and TFWT for plant leaves were measured by LSC (Quantulus 1220) on water extracted from frozen samples using a freeze-drying vacuum system equipped with a liquid nitrogen trap. Plant leaf OBT levels were obtained by combustion of rinsed freeze-dried samples using a Parr combustion system, while soil OBT values were obtained using a tube furnace combustion system. Combustion water was distilled before being counted by LSC (Quantulus 1220). HTO activity concentrations were found to range between 1.4 and 2.0 Bq/L (MDA = 0.5 Bq/L) in surface water and soil samples. TFWT values were less than the minimum detectable activity (MDA = 3.5 Bq/L) in plant leaves. In contrast, OBT activity concentrations (MDA = 5 Bq/L) ranged from 5.7 to 17.1 Bq/L in plant leaves and 8.3–20.7 Bq/L in surface soil (0–5 cm depth). The overall OBT activity concentrations were higher in the London and the Cornwall areas. Lower levels were measured near Thunder Bay, Kapuskasing and Elliot Lake. There was no obvious relationship between soil OBT activity concentrations and soil types. The results provide the current tritium (HTO, TFWT and OBT) baseline values in Ontario. These values will be helpful for use as background locations for the evaluation of past and future environmental tritium inputs associated with nuclear facilities, and will be taken into account when evaluating the environmental impact of nuclear facilities in Ontario. Since samples in this study were primarily taken in wooded areas, some questions remain regarding the possibility that soil samples in open, non-wooded areas could show different HTO and OBT contents than those presented in this study. Highlight: Five representative background sites in Ontario, based on their geological characteristics and residential populations, have been selected for this study. Tritiated water (HTO), tissue free water tritium (TFWT) and organically bound tritium (OBT) activity concentrations in soil and plant leaves were measured to quantify the current tritium baseline.